Glutathione S-transferase polymorphism in ethnic groups living in Eastern Siberia - E. V. Belyaeva; O. A. Yershova; T. A. Astahova; O. V. Bugun (Вавиловский журнал генетики и селекции)
The role of glutathione S-transferase for the life of the cell and the entire organism is related to their participation in the processes of detoxification of xenobiotics and antioxidant protection. Genetic variability of glutathione S-transferases appears in the form of different enzymatic activity of the corresponding protein products. In this study, a comparative analysis was conducted on the frequency of genotypes of three genes in the glutathione S-transferases gene superfamily (GSTM1, GSTT1, GSTP1) from representatives of two ethnic groups, Russian and Buryat. To this end, genetic typing of DNA samples was performed by polymerase chain reaction. Statistically significant differences in the frequency of occurrence of alleles A, B, C of the GSTP1 gene (р = 0.026) were found between the groups of teenagers compared. It was found that the frequency of the allele A, which codes for the active variant enzyme, is significantly higher in the Buryat ethnic group (p = 0.012). The allele B, the product of which is a “slow” version of the enzyme, was significantly more common in the Russian ethnic group (p = 0.014). In the GSTM1 and GSTT1 genes, no statistically significant differences in the frequency of occurrence of “zero” and “functional” genotypes between the compared groups of teenagers were found. However, there was a tendency to increase in the frequency of the “zero” genotype of the GSTM1 gene in the Russian ethnic group. In addition, the frequency of the “zero” genotype in two genes GSTM1 and GSTT1 at once was almost two times higher in the Russian ethnic group than in the Buryat ethnic group.